2002
DOI: 10.1590/s0034-89102002000700011
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico de dezesseis anos de uma unidade de terapia intensiva pediátrica

Abstract: Descritores ResumoObjetivo Revisar e descrever os dados epidemiológicos dos pacientes admitidos em uma unidade de terapia pediátrica brasileira (UTIP) e compará-los aos aspectos clínicos associados aos índices de gravidade e mortalidade. Descrever as características desses pacientes, incluindo os dados demográficos, prevalência de doenças, índices de mortalidade e fatores associados. Métodos Os dados foram coletados retrospectivamente de todos os pacientes admitidos na UTIP de um hospital universitário entre 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
16
2
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 14 publications
7
16
2
19
Order By: Relevance
“…The mean length of stay in hospital was 6.9 ± 5.5 days. These data are similar to those in previous studies [6][7][8][9] .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The mean length of stay in hospital was 6.9 ± 5.5 days. These data are similar to those in previous studies [6][7][8][9] .…”
Section: Resultssupporting
confidence: 93%
“…This is close to what was found by other authors, including Sfoggia et al 17 and Einloft et al 7 , who found a frequency of surgical admissions of 25.8% and 20.3%, respectively. Regarding the involvement of organs and systems, Khilnani et al 9 and Linhares et al 12 reported results similar to those found in our study.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations